“Neuropatologia Polska”. The journal and its topics in the first decade of existence (1963–1972) - Piotr Paluchowski; Jacek Gulczyński; Mateusz Michalski; Teresa Wierzba-Bobrowicz; Dorota Sulejczak; Ewa Iżycka-Świeszewska (Folia Neuropathologica, 2023)
In this article authors would like to present the history of the “Neuropatologia Polska” journal (since 1994: “Folia Neuropathologica”) in its first decade of existence. It outlines the circumstances surrounding the creation of the journal and shows how it evolved in the first years. The vast material analysed from the consecutive issues of the journal in the years from 1963 to 1972 was subjected to statistical and content analysis. From its first year, the journal has included works of a very high substantive level and a wide range of topics. The authors presented the results of contemporary research in many areas. The “Neuropatologia Polska” journal (later “Folia Neuropathologica”) set paths for the development of neuropathology in clinical and experimental aspects. What is very important, it created a platform for international cooperation in many fields, included researchers and scientists from Western countries and foreign academic centres in difficult times. This article was created on the 60th anniversary of creation of “Neuropatologia Polska”.